Efficient 4-Nitrophenol sensor development based on facile Ag@Nd2O3 nanoparticles. (September 2018) - Rahman, Mohammed M.; Wahid, Abdul; Alam, M.M.; Asiri, Abdullah M.
Graphical abstract: Highlights: Ag@Nd2 O3 nanoparticles prepared by facile wet-chemical method. Highly sensitive 4-nitrophenol chemi-sensor by reliable I–V method. Chemi-sensor exhibits the lower detection limit within short response time. Practically analyzed the real environmental samples. Effective chemi-sensor for health care and environmental fields. Abstract: 4-Nitrophenol (4-NP) is toxic organic compound and was determined by silver doped neodymium oxide aggregated nanoparticles (Ag@Nd2 O3 NPs). The aggregated nanoparticles (NPs) were prepared by wet chemical process and was characterized by UV–vis, FT-IR, XRD, FE-SEM, XPS, and XEDS techniques. The NPs were applied to the glassy carbon electrode (GCE) with the help of conducting binders called nafion. The fabricated Ag@Nd2 O3 /Nafion/GCE has good selectivity and sensitivity and is linear over concentration ranging from 1.0 pM –0.1 mM. The sensitivity value of the fabricated GCE was 0.2215 μA μM −1 cm -2 . The above mentioned electrode has lower value of limit of detection which was 0.43 pM. The electrode prepared was simple and was easy to handle with electrometer. In shortly, the prepared chemical sensor was environment and eco-friendly for the detection of various toxic and hazardous chemical pollutants to promote friendly and green environment.